Features of the Common Myna in Green Areas of Almaty - Birlikbay , Yeszhanov; Nurlan, Baymurzaev; Sayat, Sharakhmetov; Askar, Mautenbaev; Bekzat, Tynybekov; Alibek, Ydyrys (International Journal of Poultry Science, 2019)
Background and Objective: The common myna is native to southern Asia and has been found in Kazakhstan since 19611. This article aimed to determine the current state of the localization of the common myna (Acridotheres tristis L.) in urban areas. This bird quickly adapts to new environments and has become a real synanthropic species. Due to its adaptive assimilation, the myna, which is a new member of the urban ornithofauna, some of the birds found in the city began to displace. However, the number and location of Acridotheres tristis L. have not been specifically studied. Materials and Methods: Common mynas were studied in four green zones of Almaty City. The study was conducted in accordance with commonly accepted classical ornithological methodologies, including visual observations, e.g. with 30 min of observations in one location and a 5 min census on certain routes. A total of 109 h were spent in the above mentioned green zones. Results: Currently, common mynas are widespread in all areas of the city and the research areas and the distribution of the common myna was unevenly distorted and quantitatively variable. In addition to determining the number of birds that reside with common mynas and factors that threaten the safety of common mynas, the impacts of the species on the environment, including competition with other bird species, were studied. Conclusion: The common myna population in Almaty is healthy and these birds have quickly adapted to the moderate belt climate and are gradually spreading to the north. In addition, they are displacing local birds that reside in the cities of Kazakhstan.